高齢者の腰痛症者に及ぼす水中運動の影響 - 藤島, 和孝; 赤嶺, 卓哉; 増本, 賢治; 堀田, 昇 (日本生理人類学会誌, 2000)
The purpose of this study was to assess the physiological effects of aquatic exercise on lower back pain in elderly patients. Lower back pain is caused by such factors as reduction in muscle strength, loss of flexibility, poor posture, stress, and obesity. In this study, aquatic exercise was carried out in 70 minute sessions, twice a week over a period of 4 months. Eighteen subjects (age:61.0±5.5, weight:59.9±8.2, %fat:22.4±58.8) participated in the study. The anthropometry of the subjects studied such as their body weight, triceps skinfold thickness, subscaper skinfold thickness, and %fat were decreased as a result of the aquatic exercise. Cardiorespiratory function, anerobic capacity improved significantly and VO2max improved slightly. The subjects showed significant improvements in muscle strength such as in right knee extension and left knee extension. Flexibility in standing trunk flexion and upper body flexibility improved significantly. In a standardized questionaire set by The Orthopaedic Society of Japan used prior to and following the 4 month period of exercise, a significant increase was seen in the number of points of the categories ″Subjective Symptoms″ and ″Daily Activities″ as well as a significant increase in the total number of points. According to a post testing questionaire concerning the aquatic exercise program, all subjects felt ″Good″ or ″Great improvements″ in their physical condition. In addition, in a questionaire regarding the efficacy of PNF training under water, ten of the eleven male respondents indicated ″Very Effective″ or ″Effective″ and none of them indicated ″Bad Effect″. These results (improvements in muscle strength, flexibility, subjective symptoms and daily activities) suggested that the aquatic exercise was effective for elderly patients suffering from lower back pain.